397 High Flow Nasal Cannulae Cause Less Nasal Trauma Compared to Nasal Continuous Positive Airway Pressure in Preterm Infants. (October 2012) - Collins, C
Abstract : Background: Nasal continuous positive airways pressure (NCPAP) facilitates extubation but can cause nasal trauma which ever device is used. The burden of nasal trauma is poorly defined in the literature. Nasal trauma often occurs in the smallest infants who require the longest duration of respiratory support. Nasal injury is usually mild and resolves with cessation of NCPAP. It can however lead to permanent disfigurement with long term functional sequelae. High flow nasal cannulae (HFNC) offer an alternative modality of respiratory support and may allow for decreased infant handling and less nasal trauma than NCPAP. Methods: 132 ventilated infants < 32 weeks of gestation were randomised to receive either HFNC (N=67) or NCPAP (N=65) following primary extubation. A nasal trauma score was adapted from Kaufman [EPAS 2007:61390] and validated. Nasal trauma scores were recorded for 7 days post-extubation (Figure 1). Each episode of prong repositioning was recorded for 72 hours post-extubation. Results: Conclusions: HFNC results in significantly less nasal trauma and fewer prong repositions than NCPAP. These are important benefits that should be considered especially if HFNC and NCPAP are demonstrated to be equally efficacious for post-extubation respiratory support in preterm infants.